ANTIMICROBIAL ACTIVITY OF METHANOLIC EXTRACTS OF SAMBUCUS EBULUS AND URTICA DIOICA AGAINST CLINICAL ISOLATES OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS - Salehzadeh, Ali; Asadpour, Leila; naeemi, Akram sadat; Houshmand, Elham (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Increase in the emergence of drug - resistant pathogens led to the development of natural antimicrobials. In this study the antimicrobial effect of methanolic extracts of Sambucus ebulus and Urtica dioica on 16 skin and wound infections isolates of methicillin resistant S. aureus have been studied. Material and Methods: Solvent extraction procedure was done using soxhlet apparatus for extracting antimicrobial agents from freeze dried plants. Antibacterial activity was measured using agar well diffusion method.Results: The MIC of Sambucus ebulus and Urtica dioica extracts against the standard strain of S. aureus ATCC 6538 were determined using the micro dilution method at 15 mg and 20 mg respectively. All the test bacteria were found sensitive to the Sambucus ebulus extract and only one isolate was resistant to Urtica dioica extract.Conclusion: Extracts of Sambucus ebulus and Urtica dioica possess antibacterial potency against MRSA isolates and may be used as a natural antiseptics and antimicrobial agents in medicine.